Optimalisasi Motivasi dan Hasil Belajar Peserta Didik pada Mata Pelajaran Prakarya dan Kewirausahaan KD 3.7/4.7 Materi Sistem Produksi Usaha Kerajinan dari Bahan Limbah Berbentuk Bangun Ruang Melalui Model Project Based Learning Metode Latihan Keterampila - Dewi Ernita (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increase in motivation and learning outcomes of students in the Craft and Entrepreneurship subject on the topic of Craft Business Production Systems from Waste Materials in the Shape of Building Spaces through the Projects Based Learning model of Skills Training Method (Drill Method) in the Even Semester of the 2021/2022 Academic Year. in class XI.IPS.2 MAN 2 Payakumbuh City, West Sumatra. This research was conducted using the Classroom Action Research method which consisted of two cycles, in which each cycle consisted of: planning, action, reflection, and evaluation. This research was conducted from January s.d. March 2022. The data is processed in each cycle and then analyzed using percentages. The results obtained from this study are approaches, Projects Based Learning models, discussion methods, can increase students' motivation and learning outcomes. This is evident from the increase in students' motivation from 70.19% in Cycle I to 73.81% in Cycle II, while the learning outcomes for knowledge competence gained in Cycle I increased from 80.88 to 85.88 in Cycle II and learning outcomes for skill competence rose from 85.29 in Cycle I to 97.05 in Cycle II. The conclusion obtained from this study is that the use of the projects-based learning model approach to skills training methods can increase students' motivation and learning outcomes.